MAKING FISHING GAME TO LEARN VOCABULARY FOR KINDERGARTEN STUDENTS - Siti Linda Kurniani; Safra Apriani Zahra (INOVISH JOURNAL, 2016)
Abstract : Vocabulary is one of important component in teaching English, in addition to other components such as structure, pronunciation and intonation. Mastering the vocabulary is very important especially for students who learn foreign languages. In general, students who just start to learn English need knowledge of vocabulary because with a good and adequate vocabulary, the students will be able to understand the meaning of English. Therefore, the use of learning media in learning will surely help these learners understand the lesson well. Besides, they can also learn English in a more effective and interesting way. The research question was â€œIs there a fishing game to help students learn vocabulary? Meanwhile, the objective of this final project was to make Fishing Game to help the students in learning vocabulary, especially Alphabet and Number for Kindergarten students. In this study, descriptive method was used. It described what existed to find new facts or meaning. This project results were a set of fishing game consists of a Fish Pond, thirty six sets Fish of Alphabets and Numbers, and four a Fishing Rod. This game can be used in classes during learning-teaching process to help the students memorize Alphabets and Numbers. By using this game, the students can learn vocabulary in a more interesting and effective way.Â Keywords: Fishing Game, Vocabulary, Kindergarten, Alphabets and Numbers.